Mechanisms of Administrative Offenses of Minors - Karipbaev, Zhasulan; Bozhkarauly, Altay (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
The mechanism of illicit behavior of minors in administrative offenses has a complex morphological footprint. In its essence, it involves not only the administrative action itself, but also its direct causes, that are the necessary attributes of the offense, that are presented in the form of administrative representation, that is the subject to administrative responsibility. It goes without saying that in this case, it should be remembered that in the case of administrative law, there are alternative measures to minimize administrative incentives by juvenile delinquents in terms of administrative responsibility. Thus, it is obvious that no external act of conscious behavior will be by itself or spontaneously; it is almost always ready for a long-term period of motivation, action planning and decision-making on action that arises sooner or later. As a rule, before this kind of act, the complex functioning of the mental function of the subject gradually forms the direction of action and its actual implementation. At the same time, the environment of the juvenile as well as the circumstances in which he or she lives are of great importance.